Possibilities of cooperation and association among non-wood forest product collectors in the region of Šumadija and Western Serbia - Nedeljković Jelena; Košanin Aleksa; Nonić Dragan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
The collection, purchase, processing, and selling of non-wood forest products (NWFPs) have a long tradition in Serbia. Associations of NWFP collectors play a role in the development in this sector by improving market access, promoting sustainable harvesting practices, etc. This paper aims to explore the perspectives of NWFP collectors on cooperation and association membership. The data was collected in the Šumadija and Western Serbia region, where 289 household representatives involved in NWFP collection were surveyed from April to May 2022. Approximately half of the respondents (53.2%) do not collaborate with other collectors. When cooperation does occur, it primarily involves information exchange (93.4%), joint collection (79.5%), and transportation (69.5%). Although nearly all collectors (99.3%) are not members of any association, the majority (98.1%) recognize the lack of adequate representation of their interests. To improve attitudes towards association membership, it is necessary to increase collectors’ awareness of the benefits and opportunities provided by these associations, while improving the effectiveness of interest representation.